Penerapan Sistem Agribisnis Peternakan Kambing Jawa Randu dalam Kerangka Pengembangan Wilayah Kecamatan Karangpucung, Kabupaten Cilacap - Dewi Norytyas Prihatiningrum (Department of Urban and Regional Planning, Diponegoro University, 2013)
Karangpucung sub-district is centers of Jawa Randu Goats ranch developed by most of the local community. Thet kind of Jawa Randu goats is the result of a cross Jawa goats with Ettawa. The result of Jawa Randu goats ranch having high devotees, not only from local people but also from outside area even outside the province. Consumers of Jawa Randu goats derived from Banyumas, Banjarnegara, Purworejo, Kebumen, West Java and city and the surrounding area. However, development costs during this is only done in a traditional manner that hereditary and some even still are subsistence or only to even support their own, and have not oriented business. Of some of the problems, can be made the formulation of the problem, namely that the activities of the development of